Zur Ikonizität deutscher Zwillingsformeln - Gaweł, Agnieszka (Linguistik Online, 2017)
In this paper we present a corpus analysis of the influence of sequential iconicity on the linear order of German irreversible binomials. The analysis provides evidence for the thesis that semantic and pragmatic factors determining the linear order of binomials can be interpreted as examples of sequential iconicity which subsumes several cases of iconic coding: the linear order of linguistic units reflecting the structure of the extralinguistic reality, the cognitive pro-cesses and the sociocultural coding.